Rationalitation of the Organization of the Local Russian Self-Government. /Racionalización de la organización del autogobierno local ruso. - FAATOVNA NIGMATULLINA, ELMIRA; AIDAROVNA ZALIALETDINOVA, DIANA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article is devoted to the organization of local self-government in the context of the search for new rationality. Moving on to the individual powers of local self-government bodies, the authors discuss the need to modernize management in municipalities, which is designed to guarantee every citizen the right to participate in the implementation of local self-government. In relation to the main functions of local self-government bodies contained in the legislation (in ensuring a favorable environment, collective actions), the authors give judicial practice as an example and identify problems of law enforcement, stated in the final part of the work.RESUMEN El artículo está dedicado a la organización del autogobierno local en el contexto de la búsqueda de una nueva racionalidad. Pasando a los poderes individuales de los órganos de autogobierno local, los autores discuten la necesidad de modernizar la gestión en los municipios, que está diseñada para garantizar a todos los ciudadanos el derecho a participar en la implementación del autogobierno local. En relación a las principales funciones de los órganos de autogobierno local contenidas en la legislación (en asegurar un entorno favorable, acciones colectivas), los autores dan como ejemplo la práctica judicial e identifican problemas de aplicación de la ley, expresados en la parte final del trabajo.